Physicians' motivation in the Ministry of Health and Population - Egypt: challenges and opportunities. - Alsawahli, Heba (AUC Knowledge Fountain, 2019)
Amidst the different problems encountered at the Egyptian Ministry of Health (MOHP) and Population, the issue of physicians' retention is on the rise. The Egyptian public health system reportedly lost more than five percent of its workforce of physicians in less than three years (2016-2018), as documented by CAPMAS and the Egyptian Medical Syndicate in 2016. Clinicians are not only skipping the practice from the MOHP, but even a number of academic institutions report a decreasing number of candidates interested in pursuing such a previously known attractive career path as faculty in the different schools of medicine. Figures about the increased migration rates of Egyptian doctors are also striking, partly attributable to the various hurdles they face within the MOHP. Adopting a qualitative research approach, the motives of clinicians to practice in the public sector are investigated in this study. Theories and definitions of motivation are explored to explain how motivation starts and what is required to maintain it. The research showed that various factors push and pull Egyptian doctors from practice in the MOHP; their individual motivations highly change due to organizational and cultural conditions. Reported constraints included the challenging career development opportunities, the inadequate infrastructure, as well as inefficient management, and inadequate legislative environment. Doctors’ attrition, shifting to private practice and migration to the Arab and Gulf countries are some commonly encountered consequences of low motivation. Physicians' shortage is an issue in both developing and developed countries. Securing the needed human resources for the health care services is vital. Several policies were developed to bridge this gap, including performance-based financing and training complementary personnel. In Egypt, some measures were adopted such as obliging fresh graduates to fill in the gaps and piloting the delegation of certain tasks to mid-level personnel. However, as the current study indicates, additional expenditure on health is the real step that the Egyptian health system should implement to ensure healthier living conditions for the most underprivileged citizens. Reforms in governance and administration should follow, with changes to medical education and training entities.